"I Will Never Leave You nor Forsake You": An Intertextual Study of the Logic between the Exhortation in Hebrews 13:5a and the Quotation in Hebrews 13:5b - Coetsee, Albert Johannes (Neotestamentica, 2023)
This contribution investigates the logic between the exhortation in Hebrews 13:5a and the words of the quotation in Hebrews 13:5b that support the exhortation. There seems to be a slight jump between the explicit exhortation not to love money and the quotation presumably assuring divine presence. The first section of the article investigates anew the most probable Vorlage of the quotation in Hebrews 13:5b to determine how the words were used in its original context. The article finds that a version of Deuteronomy 31:6LXX is the most likely Vorlage, and that Philo, Conf. 166 contains the same quotation verbatim. The second section of the article investigates the reasons for the similarities between Hebrews and Philo, and whether Philo’s use of the quotation influences the interpretation of Hebrews 13:5. Based on these findings, the article concludes that the author of Hebrews uses Deuteronomy 31:6LXX not only as a reference to divine presence but also divine protection.